Colors of "La Gloria" - Lübbert, Andrés; Luna, Omar Miguel (Belgium, 2010)
A film about three artists who live and create in the La Gloria neighborhood of the city of Mendoza, Argentina. Through their art they fight the stigma of violence in the poorer neighborhoods of Argentinian cities and also highlight the important role of art as a tool for social change.
Verzio Film Festival Submission
Keywords: Documentary films